Kepatuhan Diet Menggunakan Beras Coklat Terhadap Glukosa Darah Dan Lemak Tubuh Pasien Diabetes Mellitus - Fitrah Fitrah; Andi Dini (Lembaga Pengembangan Kinerja Dosen, 2022)
Brown rice contains more magnesium, more fiber, and a lower glycemic index than white rice, which is thought to prevent increasing blood glucose and reduce body fat. This study aimed to determine the relationship between adherence to brown rice diet with fasting blood glucose levels and body fat composition in Type 2 DM patients. This study was a quasi-experimental study with one group pre-test and post-test design in 18 patients of type 2 DM that met the inclusion criteria. The research subjects were given a diet intervention for three consecutive months. Examinations of fasting blood glucose and body fat composition were carried out before and after the intervention. During the dietary intervention, 94.4% of respondents complied with the diet. After the intervention, there was a decrease in blood glucose control from the poor category by 27.7%, thepercentage of body fat in the high category by 22.2%, and the visceral fat index in the high category by 22.2%, but there was no relationship between dietary compliance and fasting blood glucose, total body fat, and visceral fat (p=0.339, p= 0.496, p=0.551, spearman). In brief, a brown rice-based diet in Type 2 DM can reduce fasting blood glucose levels and body fat composition, but there is no statistical relationship between dietary compliance with these three parameters.